From compliance to constraint: How digital regulation impacts productivity and innovation in Europe - Fredrik Erixon; Oscar Guinea (EconPol Forum, 2024)
A big part of the EU-US productivity gap is due to the EU investing less in ICT-related tangible and intangible capital. These lower investments are partly explained by EU digital regulations limiting companies' access to modern endowments like data. Limits to these endowments push EU firms towards a market specialization in less ICT-intensive activities. The EU has overlooked the full impact of digital regulations by focusing on compliance over these behavioral effects. The EU must reduce digital regulation restrictiveness to increase the contribution of digital technologies to productivity growth.
Keywords: 330